2013
DOI: 10.1063/1.4809988
|View full text |Cite
|
Sign up to set email alerts
|

The structures of thin layer formed by microphase separation of grafted Y-shaped block copolymers in solutions

Abstract: We study the structure formation of grafted Y-shaped block copolymers in solutions via dissipative particle dynamics simulations. We systematically examine how the solvent quality, the grafting density, and the incompatibility between polymer blocks affect the morphology of the grafted layer. The layer thickness and the lateral domain size and inhomogeneity of the layer structures are analyzed. A power law, hlayer ~ σ(n), is found between the layer thickness (hlayer) and the grafting density (σ), which shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…The simulated annealing technique was used in the simulations. , The “single-site bond fluctuation” model of polymers was applied. , Details of the model system and simulation procedure are given elsewhere. ,, Only a brief account is given here.…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulated annealing technique was used in the simulations. , The “single-site bond fluctuation” model of polymers was applied. , Details of the model system and simulation procedure are given elsewhere. ,, Only a brief account is given here.…”
Section: Models and Methodsmentioning
confidence: 99%
“…We also found that the morphologies of the grafted polymers are affected by the solvent quality and selectivity, grafting density, as well as the incompatibility between different polymers. More recently, the structures of thin layer formed by grafted Y-shaped block copolymers in different solutions, such as polymer layer thickness and domain size, have been investigated in detail by Gao et al 16 using dissipative particle dynamics. Different with our simulation results, they found that all of the surface structures are irregular and lack long-range order, even though the grafting points are fixed and with uniform distribution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The studies about end‐grafted diblock copolymer brushes were carried out almost simultaneously with mixed homopolymer brushes. Theory and simulations on this important type of binary polymer brushes have been extensively reported in past two decades . Similar to mixed homopolymer brushes, diblock copolymer brushes with enough incompatibility between the two blocks also experience microphase separation.…”
Section: Binary Polymer Brushes On Flat Substrates: Methodology and Cmentioning
confidence: 99%
“…In addition, the same scaling law in poor solvent becomes H 1 = d∝N 1/2 ( τ 3 / χ ) 1/6 ( τ is a parameter which indicates the solvent quality). Lately, the nanostructures of grafted Y‐shaped copolymers were investigated via MC simulations using simulated annealing technique and DPD simulations . Both of these simulations systematically examined how the solvent quality, the grafting density, and the incompatibility between the polymer blocks affect the morphology of the grafted layer.…”
Section: Binary Polymer Brushes On Flat Substrates: Methodology and Cmentioning
confidence: 99%
“…Patterned surfaces created by block copolymers have been thoroughly studied for use in biological, electronic, and membrane applications. As useful as block copolymers are, they have several significant drawbacks. First, the coatings are generally spin coated, meaning that only planar surfaces can be used.…”
mentioning
confidence: 99%